The royal ménagerie: a collection of the best caricatures which have appeared in Paris since the late Revolution. - Tilt, Charles (Ménagerie royale, 1831)
On p. [2-4] of advertisement: The 24 caricatures appeared in Paris after the revolution of 1830 and the editor provides a short commentary on most of the plates, explaining allusion that might escape an English audience.
Captions under plates in French and English.
On p. [2-4] of advertisement: The 24 caricatures appeared in Paris after the revolution of 1830 and the editor provides a short commentary on most of the plates, explaining allusion that might escape an English audience.
Gift of Anne Willan and Mark Cherniavsky
Keywords: Kings and rulers. / fast / (OCoLC)fst00987694; French wit and humor, Pictorial. / fast / (OCoLC)fst00934847; Caricatures and cartoons. / fast / (OCoLC)fst00847532; Caricatures and cartoons / France.; French wit and humor, Pictorial.; France. / fast / (OCoLC)fst01204289; France / Kings and rulers / Caricatures and cartoons.; France / History / Charles X, 1824-1830 / Caricatures and cartoons.; Caricatures and cartoons. / fast / (OCoLC)fst01423691; History / fast / (OCoLC)fst01411628